2013
DOI: 10.3390/arts2040350
|View full text |Cite
|
Sign up to set email alerts
|

Saharan Rock Art: Local Dynamics and Wider Perspectives

Abstract: Rock art is the best known evidence of the Saharan fragile heritage. Thousands of engraved and painted artworks dot boulders and cliffs in open-air sites, as well as the rock walls of rockshelters and caves located in the main massifs. Since its pioneering discovery in the late 19th century, rock art captured the imagination of travellers and scholars, representing for a long time the main aim of research in the area. Chronology, meaning and connections between the different recognized artistic provinces are s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 46 publications
0
15
0
2
Order By: Relevance
“…Hanotte et al, ; Pérez‐Pardal et al, ), especially for highly mobile species with few faunal remains (Almathen et al, ); evidence of aquatic resource exploitation; rock art (e.g. Gallinaro, ; Guagnin, ); and geomorphic and ethnoarchaeological evidence of herding (e.g. Biagetti, ; Zerboni & Nicoll, ).…”
Section: Discussionmentioning
confidence: 99%
“…Hanotte et al, ; Pérez‐Pardal et al, ), especially for highly mobile species with few faunal remains (Almathen et al, ); evidence of aquatic resource exploitation; rock art (e.g. Gallinaro, ; Guagnin, ); and geomorphic and ethnoarchaeological evidence of herding (e.g. Biagetti, ; Zerboni & Nicoll, ).…”
Section: Discussionmentioning
confidence: 99%
“…However, different types of vegetation, drainage or different ages of anthropogenic features were not disaggregated for this study, nor different types of local and inherent spatial dependence (e.g., clustering or repulsion) were not considered in the point process model [72][73][74]. Furthermore, the model so far does not include the limited number of rock art sites published (e.g., [11]) covering the last 5000 years.…”
Section: Discussionmentioning
confidence: 99%
“…3000-1000 years BP [10]. On the other hand, recent studies of rock art [11] and carved texts [12,13] from SW Libya have demonstrated how a landscape approach to this evidence can shed new light on late prehistoric, historical, and modern human-landscape interactions. Most archaeological data, however, come from open-air sites that have higher visibility in the landscape.…”
Section: Introductionmentioning
confidence: 99%
“…Combined with the diffusion of Tifinagh writings (a Libyco-Berber script) across the Sahara, Cameline rock art contributes to understanding the exploitation of water sources and landforms in a dramatically altered Saharan environment (e.g., Biagetti, Ait Kaci, Mori, & di Lernia 2012;di Lernia 2012). In her recent review of Tadrart Acacus rock art, Gallinaro (2013) has introduced the term 'Modern Camel', which includes the artworks produced today along with subjects of recent items of material culture such cars, guns, and the like.…”
Section: Camel Art Of Desert Peoplesmentioning
confidence: 99%